Ability of the ankaferd blood stopper® to prevent parenchymal bleeding in an experimental hepatic trauma model - Aysan, Erhan (e-Century Publishing Corporation, 2010)
Hepatic parenchymal bleeding (HPB) is a major problem following both trauma and elective hepatic procedures. The present study investigated the effect of the Ankaferd Blood Stopper® (ABS) on HPB. Method(s): A total of 20 rats were used. After creating a laceration model in the left lateral hepatic lobe, the area was compressed for 3 minutes with the ABS in the rats in group 1 (n=10) and with 0.9% NaCl-soaked gauze in the rats in group 2 (n=10). Results: The mean change in haematocrit levels between baseline and the 24 hour values in group 1 was lower than group 2 (p=0.045). The mean perioperative bleeding in group 1 was lower than group 2 (p=0.003). The histopa-thologic evaluation revealed that there were no differences between the groups with respect to areas of necrosis (p=0.107) or inflammation (p=0.135). Conclusion: Although the ABS does not stop HPB completely, it ensures a statistically significant reduction in HPB.